2010
DOI: 10.1063/1.3481377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of O3 and H2O oxidants on C and N-related impurities in atomic-layer-deposited La2O3 films observed by in situ x-ray photoelectron spectroscopy

Abstract: The effect of H2O and O3 oxidants on the behavior of residual C and N-related impurities as well as Si out-diffusion and interfacial layer formation in atomic-layer-deposited La2O3 films grown at 250 °C were examined using in situ x-ray photoelectron spectroscopy. The silicate formation was suppressed in a La2O3 film grown using O3 compared to that deposited using H2O, but interfacial layer growth was enhanced. The accumulation of C and N-related residues with low binding energy, which originated from incomple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Moreover, the variation of the degree of reduction of the percentage composition of C impurity for sample A is more severe than that for the other samples after annealing. This result indicates that the film using O 3 as an oxidant is more prone to achieve the saturation adsorption reaction and has a greater advantage in controlling the C impurity level compared with the film using H 2 O as an oxidant [19]. On the other hand, the percentage composition of N impurity for as-deposited sample D is higher than that for the other samples shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the variation of the degree of reduction of the percentage composition of C impurity for sample A is more severe than that for the other samples after annealing. This result indicates that the film using O 3 as an oxidant is more prone to achieve the saturation adsorption reaction and has a greater advantage in controlling the C impurity level compared with the film using H 2 O as an oxidant [19]. On the other hand, the percentage composition of N impurity for as-deposited sample D is higher than that for the other samples shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…ALD is also suitable for depositions on trench-type structures. Also, for thin films, the ALD produces better uniformity and lesser defects as compared to other deposition techniques [18, 19]. These qualities make the ALD method attractive for manufacturing of future generation integrated circuits especially gate dielectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is also closely related to the type of oxygen source because the physical density, crystallinity, and film morphology, which affect the Si diffusion behavior, should be influenced by the type of oxygen source. Park et al recently reported that the O 3 process suppressed a silicate phase formation by retarding Si diffusion into the high-k film due to the higher physical density of the film, but it was also found to increase the interfacial layer growth during ALD compared to the H 2 O process [36]. The initial island-like film growth in the HfO 2 grown using H 2 O results in a smaller grain size (larger number of grain boundary through the film) in the film compared to the film grown using O 3 [30], which enhances Si diffusion into the high-k film during ALD and PDA [15].…”
Section: H 2 O Versus Omentioning
confidence: 99%
“…The previous report by Park et al expected the slightly thicker IL in the La 2 O 3 film grown using O 3 compared to La 2 O 3 film grown using H 2 O based on the XPS results. 4 However, the La precursor used in their work does not contain Si resulting in La 2 O 3 film, not La-silicate film, and the expectation based on the chemical analysis could be different from that based on the electrical measurements. 4 Considering that the physical thickness of IL in La-based films is hard to be defined due to no distinct contrast in a high-resolution transmission electron microscopy image, 12 and the IL consists of mainly SiO 2 , the similar electrical thickness of IL suggests that the difference in the physical thickness of the IL by the type of oxygen source might not be considerable.…”
mentioning
confidence: 98%
“…3 Additionally, serious Si diffusion from the substrate into the La 2 O 3 film during deposition have been reported. 4,5 The use of Si-containing Tris[bis(trimethylsilyl)amino]lanthanum, La[N(SiMe 3 ) 2 ] 3 , as a La precursor was reported as the promising way to intentionally incorporate Si in La 2 O 3 film to prevent the diffusion of Si from Si substrates. 6 Since, significant Si diffusion during ALD of La 2 O 3 film and post-deposition annealing degrades the gate controllability by increasing permittivity of the gate oxide film, the use of Lasilicate film instead of La 2 O 3 film is more attractive.…”
mentioning
confidence: 99%